Resilience Enhancing Through Microgrids Formation and Distributed Generation Allocation - Home-Ortiz, Juan Manuel [UNESP]; Sanches Mantovani, Jose Roberto [UNESP]; IEEE (Ieee, 2020)
The planning of a resilient distribution system (DS) must involve the installation of new resources and an efficient restoration scheme. In this sense, the allocation of dispatchable distributed generation (DG) and the optimal microgrids formation are efficient alternatives to obtain a resilient system. This paper presents a mixed-integer second-order conic programming (MISOCP) model to improve the resilience of the DS by the allocation of dispatchable DG and the optimal formation of radial microgrids including topology reconfiguration. The objective function minimizes the outage of loads after a high-impact and low probability (HILP) incident while the operational constraints are satisfied. Nowadays, in distribution systems several DG technologies are operating simultaneously, thus, the formulation considers a master-slave DG operation where the existent dispatchable generators are masters units while new allocated DGs are in a slave operation. Numerical results based on a real 135-bus distribution system validate the effectiveness of the proposed model.
Keywords: Microgrids formation; mixed-integer second-order conic programming; resilient distribution system